Educational tourism at La Molina National Agrarian University: An analysis of the educational experience - Lindo Angulo , Teresa (2022)
Visitor experience management involves emotional aspects, but also educational and social aspects. During this investigation, 219 people were interviewed: 9 from the UNALM Public Relations Office, and from 7 educational institutions that visit the La Molina National Agrarian University (32 adults and 178 students) to determine the social and educational aspects that influence in the experience of visitors to UNALM. During the year 2017, questionnaires and interviews were taken to obtain information, which were analyzed in groups: (a) UNALM staff, (b) teachers - school administrators, and (c) college students. In the case of teachers and students, the factor of the school of origin (public - private) was analyzed to determine the differences between these types of educational centers for this research. The main results of this research, which was carried out in a No COVID-19 context, were the following: (a) the teachers and the administrative staff of the schools recognized that the educational visits have pedagogical-academic purposes as their main motivation (the educational outing, with specific academic activities, was the most valued by private schools); and (b) students are primarily motivated by the «school trip» (recreation) rather than the educational experience of the visit.